Dam Methylation Participates in the Regulation of PmrA/PmrB and RcsC/RcsD/RcsB Two Component Regulatory Systems in Salmonella enterica Serovar Enteritidis - Sarnacki, Sebastián Hernán (Public Library of Science, 2013)
The absence of Dam in Salmonella enterica serovar Enteritidis causes a defect in lipopolysaccharide (LPS) pattern associated to a reduced expression of wzz gene. Wzz is the chain length regulator of the LPS O-antigen. Here we investigated whether Dam regulates wzz gene expression through its two known regulators, PmrA and RcsB. Thus, the expression of rcsB and pmrA was monitored by quantitative real-time RT-PCR and Western blotting using fusions with 3×FLAG tag in wild type (wt) and dam strains of S. Enteritidis. Dam regulated the expression of both rcsB and pmrA genes; nevertheless, the defect in LPS pattern was only related to a diminished expression of RcsB. Interestingly, regulation of wzz in serovar Enteritidis differed from that reported earlier for serovar Typhimurium; RcsB induces wzz expression in both serovars, whereas PmrA induces wzz in S. Typhimurium but represses it in serovar Enteritidis. Moreover, we found that in S. Enteritidis there is an interaction between both wzz regulators: RcsB stimulates the expression of pmrA and PmrA represses the expression of rcsB. Our results would be an example of differential regulation of orthologous genes expression, providing differences in phenotypic traits between closely related bacterial serovars.